Assessment of feed resources for ruminant production in northern region of Ghana - Wachiebene, S.K. (University of Development Studies, 2021)
An evaluation of crop residue utilization in smallholder crop-livestock systems was investigated in two different experiments. The first experiment determined grain and haulms yields of groundnut, and growth performance of Djallonké sheep fed groundnut haulms, cultivated at three different inter-row plant spacings of 30x15cm2, 45x15cm2, 60x15cm2 and 75x15cm2. The experiment was arranged as a randomized complete block design. A total of 60 Djallonké sheep were divided into 12 groups and replicated 3 times. In the second experiment, grain and stover yields, and nutritional quality. In the second experiment, grain, stover yields nutritional quality of leaf stripping of different varieties of maize at different physiological stages of maturity was assessed in in a 3 × 3 factorial treatment arrangement. The three maize varieties (Obatanpa, Omankwa and Abontem) and physiological stage (silking and tasselling) were arranged in a split plot design with four replications. In experiment I, plant spacing significantly (P<0.05) influenced grain and fodder yields with haulm and grain yields decreasing with increasing inter-row plant spacing. Plant spacing also affected feed intake (P<0.001), final weight (P=0.008), weight gain (P=0.010) and ADG (P=0.010). Sheep fed haulm obtained from 30x15cm2, inter-row spacing had lower feed intake compared to 45x15cm2 and 75x15cm2. However, the growth performance (final weight, weight gain and ADG) of sheep fed haulms obtained from 30 x15cm2 were superior (P<0.05) to those fed haulms from 45 x15cm2, 60 x15cm2 and 75 x15cm2 plant spacing. In the second experiment, interaction of leaf stripping and maize maturity-type was not significant on grain, stover, and fodder yields. Similarly, leaf stripping did not have any effect on (P>0.05) grain, stover, and feed yields. Moreover, leaf stripping by maize-maturity type’s interaction and its main effects had no significant effect on crude protein, neutral detergent fibre, acid detergent fibre, metabolizable energy, and in vitro organic matter digestibility The study recommends that crop-livestock farmers are encouraged to cultivate groundnut at a spacing of 30x15cm to obtain the highest results with regards to fodder yield, grain yield and growth performance of sheep. Moreover, farmers adopt the technology of leaf stripping to solve the perennial feed challenges encountered during the rainy season.